Estudo da influência da compactação no comportamento resiliente e deformação permanente de solo laterítico do Rio Grande do Sul - Pascoal, Paula Taiane (2020)
This research aims evaluate the mechanical behavior of jobsite soil, employed as pavement landfill in Rio Grande do Sul. Samples were collected from three pedological horizons and undisturbed samples from the interior and top layer landfill. It was performed physical, chemical and mechanical characterization tests, mainly resilient modulus test and permanent deformation. The resilient behavior was evaluated by eleven sets of samples, while four sets were submitted to permanent deformation tests. In addition, pavement structures were designed, considering DNER method (1981), in order to compare with structures designed by mechanistic-empirical methodology present in MeDiNa. The present jobsite was classified as clayey with lateritic behavior. The undisturbed samples from the landfill interior showed unsatisfactory resilient behavior, while the top layer presented a high resilient modulus. The models that present the most accurate correlation were Compound and Universal, since both models consider the action of confining and deviator stresses. In relation to horizons, as long as the compaction energy increases, the resilient modulus also increased. The higher the compaction energy is, the greater is the effect of confining stress on the material, whereas for normal compaction energy, the deviator stress led the samples behavior. Regarding the permanent deformation, horizon B compacted at three energies and undisturbed samples at top layer presented a satisfactory behavior, fitting in type I or II, which includes materials that tend to accommodate permanent deformation. In addition, a good correlation was obtained for Guimarães (2009) parameters for four samples submitted to permanent deformation. Finally, the designed structure accordingly to DNER (1981) would collapse by fatigue cracking before the designed life service. However, the structures designed by MeDiNa attended the established criteria for permanent deformation and fatigue cracking, corroborating for the good behavior of these soils employed as subgrade and/or base.